The Relationship between Self Regulated Learning Participants in Competency Test With Competency Test Results for Indonesian Midwives in South Sulawesi for the period July-September 2020 - Zelna Yuni Andryani.A; Nurfaizah Alza (JIDAN (Jurnal Ilmiah Bidan), 2020)
Background: Self-regulation in learning (Self-regulated learning) is a concept about how a student becomes a regulator for his own learning. Self-regulation is a process in which a student activates and supports cognition, behavior, and feelings which are systematically oriented towards achieving a goal. Learning outcomes are determined by effort rather than level of intelligence. The effort in question is that students are able to organize themselves to learn independently. Purpose: : This study aims to determine the relationship between self-regulated learning and the Indonesian midwife competency test. Methods: The research design used analytical survey with cross sectional study approach using snow ball sampling technique with a sample size of 192 respondents. Results: The results showed that there was no relationship between Self Regulated Learning and the results of the Indonesian Midwives Competency Test with a value of p = 0.236 (> α value). The need for further research on other factors that affect the results of the Indonesian Midwives Competency Test.